2016
DOI: 10.1002/app.44068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rubber interparticle distance distribution on toughening behavior of thermoplastic polyolefin elastomer toughened polypropylene

Abstract: In this study, a blend of polypropylene (PP) and two types of thermoplastic polyolefin elastomers (TPO) were prepared by melt mixing. The TPOs were either ethylene‐ or propylene‐based copolymer. The mechanical response and morphology of the blends were investigated using tensile and impact tests and scanning electron microscopy technique. There was significant increase in the impact strength of the TPO‐modified PP, which was an outcome of fine dispersion of TPO inclusions. In particular, the blends containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 38 publications
7
44
0
Order By: Relevance
“…However, PLA is often limited to low mechanical loading applications due to its brittleness. An improvement of the toughness of such brittle polymers can generally be achieved by blending with a ductile secondary phase polymer . There are a number of literatures reporting the studies of blending PLA with ductile polymers, such as polyethylene, poly(ethylene octane), and poly(ɛ‐caprolactone) .…”
Section: Introductionmentioning
confidence: 99%
“…However, PLA is often limited to low mechanical loading applications due to its brittleness. An improvement of the toughness of such brittle polymers can generally be achieved by blending with a ductile secondary phase polymer . There are a number of literatures reporting the studies of blending PLA with ductile polymers, such as polyethylene, poly(ethylene octane), and poly(ɛ‐caprolactone) .…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that samples with the azodicarbonamide foaming agent and propylenebased POE had smaller POE particles along with a more uniform particle distribution. According to previous studies on the blends of these compounds, the particle size for the POE of the propylene-base was smaller in size due to its compatibility with the PP matrix compared with the ethylene-based POE [37]. But in the foam mode, these sizes are more close to each other and for samples with a 20% of POE concentration was obtained about 200 nm.…”
Section: Cellular Structure Of Blends Foamsmentioning
confidence: 87%
“…The blending properties of these elastomers with polypropylene have been previously reported in various studies regarding their high capability to increase impact strength [34][35][36]. It has been reported that the morphology of the propagation of rubber particles inside the polypropylene matrix, as well as the rubber particle size, play the most important role in increasing the impact strength of the compound, to such extent that POEs with proper distribution can enhance the impact strength of the compound by up to 13 times [37]. Various studies have also been conducted on the foamability and morphology of polypropylene/thermoplastic elastomeric foam blends.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Toughness is a key parameter to the performance of polymers in various engineering applications . Generally, temperature is a very important external factor for the impact toughness of polymer materials.…”
Section: Introductionmentioning
confidence: 99%